2016
DOI: 10.12740/pp/onlinefirst/63787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in women with breast cancer, with particular emphasis on sexual satisfaction, future perspectives and body image, depending on the method of surgery

Abstract: The type of surgical technique does not affect the overall quality of life and sexual satisfaction. Problems with memory and attention do not correlate directly with the side effects, and as such require an independent diagnostics. Women undergoing treatment of the dominant-side breast should be the candidates for sexology consultation. There is a risk of disturbances in the body image and in the assessment of future perspectives in patients with emotional disorders observed within 3 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 0 publications
6
43
2
3
Order By: Relevance
“…Our data go along with the reported literature on distress and quality‐of‐life . Our findings confirm that breast cancer diagnosis represents a distressing event for women and that distress could be reduced but not eliminated during surgical and medical treatment.…”
Section: Resultssupporting
confidence: 86%
“…Our data go along with the reported literature on distress and quality‐of‐life . Our findings confirm that breast cancer diagnosis represents a distressing event for women and that distress could be reduced but not eliminated during surgical and medical treatment.…”
Section: Resultssupporting
confidence: 86%
“…It was suggested that more information is required for younger age groups 27 . Other studies have confirmed that after a breast cancer diagnosis, younger women need more psychological mechanisms in order to adapt to their new situation, than their older counterparts 28,29 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, compared with mastectomy, breast‐conserving surgery (BCS) causes less physical disfigurement and psychological trauma. The quality of life for patients after BCT continues to be debated . The differences in stigma and psychological condition between surgery modalities is controversial…”
Section: Introductionmentioning
confidence: 99%
“…The quality of life for patients after BCT continues to be debated. [17][18][19] The differences in stigma and psychological condition between surgery modalities is controversial. 20 Neoadjuvant chemotherapy (NACT) is defined as the application of systematic therapy prior to breast surgery.…”
Section: Introductionmentioning
confidence: 99%